Rethinking forest‐bird habitat management guidelines in the northern Lake States - R. Gregory Corace III (Wildlife Society Bulletin)
ABSTRACT Biodiversity challenges require more ecologically based approaches to habitat management of forest wildlife. Although active management is necessary for the conservation of many forest‐dependent wildlife species, some high‐severity (even‐aged) forest management practices could be improved upon with greater consideration of natural disturbance models. Using examples of 3 migratory bird species of conservation priority and for which high‐severity forest management practices are conducted in the northern Lake States (Kirtland's warbler [Setophaga kirtlandii], golden‐winged warbler [Vermivora chrysoptera], American woodcock [Scolopax minor]), I first summarize lessons learned and then illustrates how a more ecological approach to forest‐bird habitat planning and management might work. Published 2018. This article is a U.S. Government work and is in the public domain in the USA.